2016
DOI: 10.1080/08952841.2014.951231
|View full text |Cite
|
Sign up to set email alerts
|

Age at the onset of menopause and its influencing factors in Turkish women in a rural area

Abstract: This study was performed to identify menopausal age and its determining factors in women over 40 residing in the Dogubeyazit district of Agri, located in Eastern Turkey. This cross-sectional study was performed on a sample of 1,068 women, selected by simple random sampling among all district health center records of women aged 40 and greater, who were each attributed a random serial number. While 35.6% of the subjects had not yet reached menopause, 60.5% had entered it spontaneously and 3.9% surgically. Averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
4
2
Order By: Relevance
“…A systematic review indicates that the average age of menopause varies in different regions, with values reported as 50.1-52.8 in Europe, 50.5-51.4 in North America, and 43.8-53 in Latin America [12]. When specifically considering Turkey, previous studies have reported, similar to our study, an average natural menopausal age of 47.8±4.0 for the urban region and 47.4±3.7 for the rural region [6,13].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A systematic review indicates that the average age of menopause varies in different regions, with values reported as 50.1-52.8 in Europe, 50.5-51.4 in North America, and 43.8-53 in Latin America [12]. When specifically considering Turkey, previous studies have reported, similar to our study, an average natural menopausal age of 47.8±4.0 for the urban region and 47.4±3.7 for the rural region [6,13].…”
Section: Discussionsupporting
confidence: 87%
“…However, it's noteworthy that the mean ages of the women included in this study were higher than those in our study (51.3±9.4 vs. 48.2±5.9) [6].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The studied women were in menopausal stages with their aging adverse effects necessarily occur. Besides a sizable proportion of them go through pregnancy and delivered vaginally for more than three times [24] who studied age at the onset of menopause and its influencing factors in Turkish women in a rural area and supported the idea that age and menopausal state are attribution factors interfering with Kegel's effect and added that age was statistically correlated to SUI. From the researcher point of view the older age; more the problem is confronted especially in menopausal women due to decreased levels of estrogen hormone which weaken pelvic floor muscles.…”
Section: Discussionmentioning
confidence: 88%